Women"s stories implying aspects of anti-Judaism with Christological depiction in Matthew - Shin, In-Cheol (HTS teologiese studies, 2014)
This study focuses on the women’s stories that imply aspects of anti-Judaism within Matthew’s depiction of Christology, which is called Matthew’s theology. In fact, Matthew’s community opposed the Jewish system and Jewish leaders and parted from its parent body. Even though Matthew’s community was still similar to the Jewish system, it had significant differences as well. The study discusses these aspects of anti-Judaism that appear in the woman’s stories that include the genealogy of Jesus, the haemorrhaging woman, the Canaanite woman, and the women at the cross and Jesus’ tomb. This study shows proof and examples of anti-Judaism within the stories and thoroughly analyses them. Therefore, it can be confirmed that the women’s stories imply aspects of anti-Judaism with Christological depictions by Matthew’s theological tendency.